1. ## sequence

Hello,

I have the following:

$A(x)=(x+1) + \frac{1}{2x^{2}-3x+1}$

How do I find a sequence $a_{0},a_{1},a_{2},...$ such that $A(x)=\sum_{i=0}^{\infty} a_{i}x^{i}$

Thanks.

2. ## Re: sequence

Originally Posted by surjective
Hello,

I have the following:

$A(x)=(x+1) + \frac{1}{2x^{2}-3x+1}$

How do I find a sequence $a_{0},a_{1},a_{2},...$ such that $A(x)=\sum_{i=0}^{\infty} a_{i}x^{i}$

Thanks.
$\frac{1}{2x^{2}-3x+1}=\frac{1}{(1-x)(1-2x)}=(1-x)^{-1}(1-2x)^{-1}$

You could now expand using the binomial theorem.

3. ## Re: sequence

Could you elaborate a bit. It's not quite clear. I mean, when expanded how do I include x+1 ?? Assistance would be appreciated!!!

4. ## Re: sequence

Originally Posted by surjective
Could you elaborate a bit. It's not quite clear. I mean, when expanded how do I include x+1 ?? Assistance would be appreciated!!!
$(1-x)^{-1}(1-2x)^{-1}=(1+x+x^2+...)(1+2x+4x^2+...)$

After simplifying the above expression, simply add $x+1$ to obtain the required power series.